2020
DOI: 10.3390/pathogens9050366
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Vertical Transmission for Zika Virus in Aedes aegypti after Long Extrinsic Incubation Time

Abstract: While the Zika virus (ZIKV) 2014–2017 pandemic has subsided, there remains active transmission. Apart from horizontal transmission to humans, the main vector Aedes aegypti can transmit the virus vertically from mother to offspring. Large variation in vertical transmission (VT) efficiency between studies indicates the influence of parameters, which remain to be characterized. To determine the roles of extrinsic incubation time and gonotrophic cycle, we deployed an experimental design that quantifies ZIKV in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
2
7
1
Order By: Relevance
“…A recent study conducted with orally infected Ae. aegypti mosquitoes with Asian ZIKV lineage has shown that VT moderately decreased with gonotrophic cycles [18], which would agree with our results in Ae. albopictus, since we found higher prevalence in E1 progeny than in the E2 progeny.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study conducted with orally infected Ae. aegypti mosquitoes with Asian ZIKV lineage has shown that VT moderately decreased with gonotrophic cycles [18], which would agree with our results in Ae. albopictus, since we found higher prevalence in E1 progeny than in the E2 progeny.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, ZIKV VT has also been experimentally demonstrated in Ae. aegypti [16][17][18] and Ae. albopictus mosquitoes [17]; and venereal transmission, in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…It was worth noting that diapause eggs under SD photoperiod had a relative higher infection rate before 7 dpov and then MIR on 70 dpov would have been minimal, even zero, in GC1, suggesting that the virus infectivity and RNA copy number decreased with time and no virus replication occurred in the eggs finally. These results corroborated the findings of a great deal of previous work (Manuel et al, 2020 ). Despite the trend of rapid decreasing MIRs, vertical transmission was observed during GC1 (Chaves et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…During infection in female mosquitoes, the virus can be located in different tissues, but mainly in the gut, salivary glands, and ovaries ( Sá-Guimarães et al., 2021 ). Ovaries infection is of paramount importance to maintain the vertical transmission of arboviruses, even if at low rates ( Thangamani et al., 2016 ; Manuel et al, 2020 ; Nag et al., 2021 ). Therefore, evaluating physiological and molecular changes in mosquito ovaries due to arbovirus infection, especially those affecting life-history traits related to vertical transmission, might provide new insights to design innovative vector control approaches.…”
Section: Introductionmentioning
confidence: 99%